Debtor and creditor : cases, notes, and materials - Trebilcock, M. J.; Reiter, Barry J.; Laskin, J. B. (University of Toronto Press, 1979)
Developed over a period of some six years by teachers of the subject at the University of Toronto's Faculty of Law, this book provides the first comprehensive and integrated teaching tool for the very basic field of debtor and creditor relations.